Fiziksel Dağıtım Yönetiminde Teknolojinin Rekabet Üstünlüğü Sağlamadaki Rolü - Basmacı, Ali Burak (Sosyal Bilimler Enstitüsü, 1999)
Fiziksel dağıtımda teknoloji, rekabet üstünlüğü sağlamak açısından önemli bir faktördür. Teknoloji işletmenin fiziksel dağıtım faaliyetlerine iletişim, verimlilik ve kalite boyutlarında etki yaparak, işletmeye ayrı üstünlük elde etme şansını verir. Çalışmanın birinci bölümünde, Lojistik ve Fiziksel Dağıtım kavramları, bu kavramların gelişimi, fiziksel dağıtım ile pazarlama ilişkisi ve sistem yaklaşımı altında fiziksel dağıtım ve faaliyet merkezleri anlatılmaktadır. İkinci bölümde ise, fiziksel dağıtımda bilgi teknolojilerinin kullanım yeri ve şekli, teknolojinin fiziksel dağıtım açısından rekabet üstünlüğü sağlamadaki rolü ve etkileri üzerinde durulmuştur. Üçüncü bölümde, Türk Otomotiv Endüstrisi'nde fiziksel dağıtımın önemi ve fiziksel dağıtımda teknolojinin yeri ve sağladığı avantajların incelenmesi amacı ile yapılan araştırmaya ilişkin bulgular verilmiş araştırmaya ilişkin varılan sonuçlar anlatılmıştır. Son bölümde ise çalışma ile ilgili olarak genel sonuçlar ve öneriler kısmı bulunmaktadır.

During the last years, further focusing attention on phyisical ditribution as a process rather than a series of individual activities such as warehousing, transportation, and inventory management. Hieghtened global marketing competition forced companies to consider worldwide alternatives for sourcing, manufacturing, distributing, and selling their products. Foreign competitors raised customer expectations for quality, causing many firms to adopt a "Total Quality" focus. Cycle times collapsed for product manufacture and distribution as well as for new product introduction. Information technology in the areas of data capture, communications, processing, and data analysis continued to explode. In the tougher competitive environment, relying solely on product attributes as a means of attracting and retaining customers was insufficient. Customer service, therfore, assumed greater importance for many firms, becoming a weapon for gaining compettitive advantage. Companies developed strategic alliances with customers and suppliers in order to allign resources and harmonize oprations more effectively. Third-party logistics service providers emerged as alternatives for in- house transportation, warehousing and inventory management functions. Company merger and aquisition activity accelerated through the 1980s. In many cases, integrating the phyisical distribution processes of two merged companies was a key factor for the ultimate success of the deal. Management attitudes toward employees changed during these years. Many companies found that employee empowerment or, more appropriately, employee "ownership" of an improwement process was the key to ongoing improvement. Quality improvement, unlikle productivity improvement, requries a business processs focus. It transcends functional, and often company, boundaries. The essence of quality improvement is understanding and satisfying customers' needs. VIII By focusing on the phyisical distribution, the traditional phyisical distribution view of a company is changing rapidly with the help of technological developements. Especially the effect of technology in service quality is very important. Certainly, product quality is a major component on overall customer satisfaction, but it is just part of the picture. Customer service quality is emerging as an equally popular topic in the consumer and business press as well as in research communities. As it has in all areas of today's business and social environments, the advent of the computer has also caused a revolution in physical distribution management. As the complexity of managing today's enterprise expands and the speed by which information concerning products, customers, and processes accelerates, phyisical distribution functions can have little hope for responding effectively without applying computerized information systems. The integration of the operating functions of the enterprise, solutions that accelerate ordering processes and shrink delivery time to customers, electronic data interchange (EDI) systems providing connectivity between companies, PC's (personel computers) that eliminate the guesswork involved in transportation routing and scheduling, and many others are some of areas that impacted by the computer. The use and complexity of such tools can only be expected to grow, changing the way companies have traditionally serviced their customers and provided products and how they communicate with supply channel partners. Based on the nature and types of IT structure detailed, it has been proceeded to analyze how companies can align IT tools and achieve targeted break troughs in organizational capacities and competitive positioning. Next, three posible IT solutions are explored. The first centers around IT that seeks to automate the existing operations to reduce costs or achieve productivity in a focused opeational activity. The second investigates the tactical and strategic ramifications of using IT to automat and integrate a group of business functions. The final IT solution reviews the organizational and strategic impact of implementing an IT solution that seeks to integrate the entire enterprise and probide IT linkages with channel partners. IX As the importance of timely, accurate, and complete imformation increases, imformation technology has progressively become the key link integrating the business enterprise and its phyisical distribution capabilities with its customers and suppliers. What it means that today's marketplace leaders must view IT not only as a tool to accelerate the speed of productivity of business functions through automation but also as a key enabler that provides the enterprise with the opportunity to continually activate new cultures and structures that changes the way it competes in the market place and as a chance to develope its communication alternatives and to act in a more effectively way while catching a high level of service quality. The effective application of IT in the integrated phyisical distribution networks involves imformation sharing across operations, using multiple and rebust applications linked by a communication network that is flexible and seamless. It is a series of individual applications and technologies linked by a common data and networks, a combination of tecnology and infrastructure. Actualizing the potential of today's IT systems will require companies to move beyond traditional paradigms that use computerization to manage seperately their business process. Developements in IT and the implementation of empowerment based management techniques dictate a new perspective characterized by the integration of workflows, people resources, facility, and equipment and the information technologies required to execute key phyisical distribution processes. As a principle, it can be stated that the orerational and strategic needs of the organization must be in balance with the dimensions of the imformatşon necessary for effective action and desicion-making. Simply, the organization's ability to create, collect, assimilate, access, and transfer information must in alligment with the velocity of the activities necessary to execute effectively supplier, customer service, logistics, phyisical distribution, and financial processes. Changes in the speed of the velocity can come from two directions: advancements in imformation technologies or changes in the internal and external business enviroment, or sometimes both, can render the prvious equilibrium untenable and stimulate the rate of growth in either and both dimensions. In first part of this study, the concept of logistics and phyisical distribution, and their developements had been given. The relationship between phyisical distribution and marketing had been discussed and phyisical distribution had been given as a system and its components had exploded. In the second part, the usage of information technology in phyisical distribution had been given and the effect of the tecnology in phyisical distribution for gaining competitive advantage in the marketplace had been told. In the third part, the findigs of a survey in the Turkish Automotive Industry an its conclusions had been given. Eight companies which are acting in the different areas of the industry were included in this survey. In the last part, a general conclusion of the study had been given.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1999
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 1999
Keywords: İşletme; Bilgi teknolojisi; Dağıtım; Fiziksel dağıtım; Otomotiv sektörü; Rekabet; Teknoloji; Business Administration; Information technology; Distribution; Physical distribution; Automotive sector; Competition; Technology